Precipitation phase transition in austral summer over the Antarctic Peninsula - Chyhareva, A.; Gorodetskaya, I.; Krakovska, S.; Pishniak, D.; Rowe, P. (Ukrainian Antarctic Journal, 2021)
Investigating precipitation phase transitions is crucial for improving our understanding of precipitation formation processes and impacts, particularly in Polar Regions. This study uses observational data and numerical modelling to investigate precipitation phase transitions in the western and northern Antarctic Peninsula (AP) during austral summer. The analysis is based on the ERA5 reanalysis product, dynamically downscaled using the Polar-WRF (Polar Weather Research and Forecasting) model, evaluated using regular meteorological observations and additional measurements made during the Year of Polar Prediction special observing period. We analyse three cases of extra-tropical cyclones bringing precipitation with phase transitions, observed at the Chilean station Professor Julio Escudero (King George Island, north of the AP) and the Ukrainian Antarctic Akademik Vernadsky station (western side of the AP) during the first week of December 2018. We use observed and modelled near-surface air temperature and pressure, precipitation amount and type, and vertical temperature profiles. Our results show that precipitation type (snow or rain) is well-represented by ERA5 and Polar-WRF, but both overestimate the total amount of precipitation. The ERA5 daily variability and vertical air temperature profile are close to the observed, while Polar-WRF underestimates temperature in the lower troposphere. However, ERA5 underestimates the temperature inversion, which is present during the atmospheric river event, while Polar-WRF represents that inversion well. The average weekly temperature, simulated with Polar-WRF, is lower compared to ERA5. The Polar-WRF fraction of snow in the total precipitation amount is higher than for ERA5; nevertheless, Polar-WRF represents the precipitation phase transition better than ERA5 during the event, associated with an atmospheric river. These case studies demonstrated a relationship between specific synoptic conditions and precipitation phase transitions at the AP, evaluated the ability of the state-of-the-art reanalysis and regional climate model to represent these events, and demonstrated the added value of combined analysis of observations from the western and northern AP, particularly for characterizing precipitation during synoptic events affecting the entire AP.